The influence of alcohol warning labels on consumers' choices of wine and beer - Azzurra Annunziata; Lara Agnoli; Riccardo Vecchio; Steve Charters; Angela Carla Mariani (Wine Economics and Policy, 2020)
This study aims to analyse the influence of alternative formats of health warnings on French and Italian Millennial consumers' choices of beer and wine. Two Discrete Choice Experiments were built for wine and beer and two Latent Class choice models were applied in order to verify the existence of different consumer profiles. Results show that young consumers' choices for wine and beer are influenced by framing, design and visibility of warnings. In both countries, the acceptance of warnings is higher for beer than for wine and in both cases consumers show higher utility for a logo on the front label: on the neck with a neutral message in the case of beer; on the front, without a message for wine. Latent Class choice models highlight the existence of different consumers' groups with different levels of warning influencing their choices. In order to apply policies conducting to health benefits, our results suggest the need to focus on young individuals to communicate the risks of alcohol abuse through targeted messages and, more generally, to make them aware of the potential negative effects of excessive consumption of both wine and beer.
Keywords: 330; Alcohol Warning Labels; Discrete Choice Experiment; Latent Class; wine; beer; Alkoholkonsum; Wein; Bier; Warenkennzeichnung; Konsumentenverhalten; Generation Y; Alkoholpolitik; Diskrete Entscheidung; Experiment; Italien; Frankreich